2016
DOI: 10.1590/2359-3997000000137
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, hormonal and radiological features of partial Sheehan’s syndrome: an Indian experience

Abstract: Objective: The objective of this study was to describe clinical presentation, hormonal profile and imaging characteristics of 21 patients with partial Sheehan's syndrome. Subjects and methods: This prospective study was carried out over a period of six years (2008)(2009)(2010)(2011)(2012)(2013). The evaluation of patients included clinical assessment, hormone estimations and contrast enhanced magnetic resonance imaging of pituitary. Results: We documented preservation of gonadotroph, corticotroph and lactotrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The diagnostic journey for SHS patients spans a considerable duration of 7–19 years from symptom onset to definitive diagnosis ( 8 ). Sheehan's syndrome arises from ischemic necrosis of the anterior pituitary gland triggered by postpartum hemorrhage ( 8 ), leading to pituitary hormone dysfunction, including insufficient secretion of growth hormone, thyroid stimulating hormone, gonadotropin, prolactin, and adrenocorticotropin (ACTH) ( 7 , 9 ). Predominant symptoms are associated with dysfunction of the gonads, thyroid, and adrenal cortex due to insufficient secretion of gonadotropins, thyroid stimulating hormones, and ACTH, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The diagnostic journey for SHS patients spans a considerable duration of 7–19 years from symptom onset to definitive diagnosis ( 8 ). Sheehan's syndrome arises from ischemic necrosis of the anterior pituitary gland triggered by postpartum hemorrhage ( 8 ), leading to pituitary hormone dysfunction, including insufficient secretion of growth hormone, thyroid stimulating hormone, gonadotropin, prolactin, and adrenocorticotropin (ACTH) ( 7 , 9 ). Predominant symptoms are associated with dysfunction of the gonads, thyroid, and adrenal cortex due to insufficient secretion of gonadotropins, thyroid stimulating hormones, and ACTH, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…It is primarily caused by vasospasm of hypothalamic portal vessels following postpartum haemorrhage (PPH), resulting in necrosis of the pituitary gland 1,2 . The most common hormone deficiencies in these patients are growth hormone (GH) and thyrotroph deficiency, with spared gonadotroph, lactotroph and corticotroph cells in some patients 3–5 . Despite treatment for hypogonadism, secondary hypothyroidism and cortisol deficiency, these hypopituitary patients have insulin resistance (IR), lipid abnormalities, low‐grade inflammation and endothelial dysfunction 6–9 .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The most common hormone deficiencies in these patients are growth hormone (GH) and thyrotroph deficiency, with spared gonadotroph, lactotroph and corticotroph cells in some patients. [3][4][5] Despite treatment for hypogonadism, secondary hypothyroidism and cortisol deficiency, these hypopituitary patients have insulin resistance (IR), lipid abnormalities, low-grade inflammation and endothelial dysfunction. [6][7][8][9] Low insulin-like growth factor-1 (IGF-1), hypogonadism, poorly controlled secondary hypothyroidism and glucocorticoid overuse may predispose these women to CAD.…”
Section: Introductionmentioning
confidence: 99%
“…Although Sheehan's syndrome (SS) is now rarely described from developed nations, physicians from developing nations need to keep the entity in mind wherein with modern hormone assays, and imaging diagnosis is not difficult. Atypical or partial presentation of SS is described from India; with the preservation of gonadotroph and corticotroph function,[ 1 2 ] preservation of thyrotroph has not been described.…”
mentioning
confidence: 99%
“…Because of the location of somatotroph and lactotrophs in the lateral and posterior portion of the pituitary, the location is supposed to be the most susceptible to ischemic necrosis. [ 3 4 ] However, some previous studies have reported thyrotroph involvement in 90%–100% of women with SS;[ 1 ] at the same time, preservation of thyrotroph has not been described. Some elevation in TSH has been reported in these women; it usually does not cross >20 mIU/L.…”
mentioning
confidence: 99%